Edukasi dan Pendampingan Perencanaan Struktur Bangunan Tahan Gempa bagi Aparatur Pemerintah Kabupaten Kampar - Aswara, Dana; Islah, Muhammad; Putri, Normelia (Journal of Social and Community Service, 2022)
This activity was carried out to improve the understanding of planners in the Kampar Regency Government regarding earthquake-resistant building planning. The method used was a rapid visual evaluation (Rapid Visual Screening/RVS) based on the FEMA P-154 guidelines. Socialization was carried out through the delivery of technical materials, training, and discussion sessions with participants. The results of the activity showed that most of the buildings analyzed had a structural feasibility value for earthquakes, with scores above the safe threshold. However, several parameters such as irregularity in building shape and soil type are still of concern. With this activity, it is hoped that participants will be able to understand the basic concept of earthquake-resistant structural planning and be able to apply it in the construction of government buildings in the Kampar Regency area.